Ecology - Cain, Michael L; Bowman, William D; Hacker, Sally D (Sunderland : Sinauer Associates, 2014)
The new third edition of this bestselling book remains focused on being the best teaching tool possible for students taking their first course in ecology. Revised and updated, the book features a new chapter on Behavioral Ecology, an exciting and growing subfield of ecology, and new Analyzing Data exercises in which students work with real data.
Appendix; Glossary G-1-11p.; Illustration credits IC-1-4p.; Literature cited LC-1-23p.; Index I-1-30p.
Keywords: Communities; Ecosystems; Populations